ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI DALAM MENUNJANG EFEKTIFITAS PENGENDALIAN INTERNAL PEMBERIAN KREDIT PADA BANK MANDIRI CABANG KEDIRI - Nariranti, Onnyk; Nurdiwaty, Diah; Kurniawan, Andy (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
Bank Mandiri Katamso Branch is committed to providing easy credit distribution as additional business capital for micro entrepreneurs.The research objective is to analyze the accounting information system, internal control, the role of the accounting information system in providing credit at PT. Bank Mandiri Katamso Branch. The type of research used in this research is descriptive research. The application of the accounting information system is in accordance with the SOPs in force at the branch office and in accordance with Romey's (2017) theory, internal control meets the elements of internal control according to COSO in Krismiaji (2015), the role of accounting information systems in providing credit is in accordance with the 5C analysis according to Kasmir (2008). ) regarding the granting of credit to PT. Bank Mandiri Katamso Branch